Pengaruh Nilai Tukar Rupiah terhadap Pertumbuhan Ekonomi Indonesia - Ayesa Venia; Melsya Noviriza Lutfia Asma; Syifa Az Zahra; M. Yusuf Bahtiar (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
Exchange rates are a crucial indicator in an open economy, playing a significant role in influencing international trade, investment flows, and overall macroeconomic stability. This study aims to analyze the impact of rupiah exchange rate fluctuations on Indonesia’s economic growth during the period 2014–2023. The research employs a descriptive qualitative approach using secondary data obtained from official publications of Statistics Indonesia and Bank Indonesia. The main variables analyzed include the rupiah exchange rate against the United States dollar and Indonesia’s economic growth. The findings indicate that exchange rate movements are closely related to economic growth dynamics, particularly through international trade mechanisms, production costs, and the stability of the real sector. Depreciation of the exchange rate tends to enhance export competitiveness, but it may also trigger inflation due to rising import prices. Conversely, appreciation can help control inflation but may weaken export competitiveness. Therefore, maintaining exchange rate stability is essential to support sustainable economic growth and strengthen national economic resilience.